PENGARUH GREEN INNOVATION DAN INTELLECTUAL CAPITAL TERHADAP NILAI PERUSAHAAN PADA PERUSAHAAN MANUFAKTUR - Linda Arisanty Razak; wa Ode Rayyani; Nur'Izzah Amaliah Yusuf (Value : Jurnal Manajemen dan Akuntansi, 2023)
The company is expected to be able to properly implement green innovation and intellectual capital which can increase competitive advantage and corporate image so as to increase the value of the company. This study aims to examine the effect of Green Innovation and Intellectual Capital on Firm Value in manufacturing companies listed on the Indonesia Stock Exchange. The research method used is a quantitative method with an explanatory research approach. The population in this study is financial report data and sustainable report data for manufacturing companies listed on the IDX for 2017-2021, totaling 193 companies. The data collection technique in this study used a purposive sampling technique and produced a sample of 9 manufacturing companies listed on the IDX for 5 years so that the total sample used was 45 samples. Data analysis techniques were processed using the Eviews 12 system. The results of this study indicate that the Green Innovation variable has no effect on firm value. Meanwhile, the Intellectual Capital variable influences firm value. Keywords: Green Innovation, Intellectual Capital